Kombinasi Pijat Marmet dan Kompres Hangat terhadap Pengeluaran Asi pada Ibu Nifas - Murti, Ni Putu Indu Dewi Pradnyani; Suryantara, Bima; Sari, Fatimah (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effectiveness of a combination of marmet massage and warm compresses on breast milk production in postpartum mothers. The method used is quantitative research with a quasi-experimental research design. The study's results showed a difference in the effectiveness of the combination of marmet massage and warm compress on breast milk production in postpartum mothers with a p-value of (0.032 <0.05). In conclusion, combining marmet massage and warm compresses can influence the breast milk production of postpartum mothers. Keywords: Exclusive Breast Milk, Warm Compress, Marmet Massage, Breast Milk Production